Socio-ecological impacts of extreme weather events in two informal settlements in Nairobi, Kenya - Balakrishnan, Anna K.; Otieno, Stephanie; Dzombo, Millicent; Plaxico, LaNae; Ukoh, Ebuka; Obara, Lena Moraa; Brown, Haley; Musyimi, Christine; Lincoln, Chloe; Yang, Lyla Sunyoung; Witte, Susan S.; Winter, Samantha C. (Frontiers in Public Health, 2024)
Climate change is expected to profoundly impact health and coping and widen social and environmental inequalities. People living in informal settlements are especially vulnerable to climate change as they are often located in ecologically sensitive areas more susceptible to extreme weather events (EWEs), such as floods, droughts, and heat waves. Women residing in informal settlements are especially vulnerable to climate change and related EWEs because they are more likely to experience worse health-related impacts than men but are less likely to have access to health-related services. Despite this inequality, there is a dearth of research that focuses on the impacts of EWEs on women in informal settlements. This study aims to explore the multidimensional impacts of EWEs on the daily lives of women in informal settlements through the lens of socio-ecological theory. Study data is from six monthly surveys (1 September 2022–28 February 2023) collected from a probability sample of 800 women living in two of the largest informal settlements in Nairobi, Kenya. This data is part of an ongoing longitudinal study that uses community participatory methods to investigate the effects of climate change on health and wellbeing in informal settlements by a team of 16 community health volunteers who lead data collection and provide expertise in ongoing analysis. Findings show profound impacts on women's health and wellbeing across individual, micro-, meso-, exo-, and macrosystems. These include physical and mental health, financial disruptions, property issues, social impacts, and impacts on their surrounding physical environment, such as disrupted food or water access, poor air quality, drainage issues, and safety concerns. In addition, findings highlight the critical importance of the chrono- and biosphere systems in research focused on the impacts of climate change and related EWEs among climate-vulnerable communities and marginalized populations within them.